2017
DOI: 10.1021/acs.jafc.7b03210
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Latent Polyphenol Oxidase from Apricot (Prunus armeniaca L.)

Abstract: Polyphenol oxidase from apricot (Prunus armeniaca) (PaPPO) was purified in its latent form (L-PaPPO), and the molecular weight was determined to be 63 kDa by SDS-PAGE. L-PaPPO was activated in the presence of substrate at low pH. The activity was enhanced by CuSO4 and low concentrations (≤ 2 mM) of SDS. PaPPO has its pH and temperature optimum at pH 4.5 and 45 °C for catechol as substrate. It showed diphenolase activity and highest affinity toward 4-methylcatechol (KM = 2.0 mM) and chlorogenic acid (KM = 2.7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
53
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 61 publications
11
53
1
1
Order By: Relevance
“…The results were similar to those of apricot (Derardja et al, 2017) and lily bulbs (L. lancifolium Thunb) (Yang & Wang, 2008). The enzyme kinetic parameters were calculated by using the double TA B L E 3 Effect of various inhibitors on the activity of lily bulbs PPO using catechol as a substrate.…”
Section: Substrate Specificity and Enzyme Kineticssupporting
confidence: 61%
See 1 more Smart Citation
“…The results were similar to those of apricot (Derardja et al, 2017) and lily bulbs (L. lancifolium Thunb) (Yang & Wang, 2008). The enzyme kinetic parameters were calculated by using the double TA B L E 3 Effect of various inhibitors on the activity of lily bulbs PPO using catechol as a substrate.…”
Section: Substrate Specificity and Enzyme Kineticssupporting
confidence: 61%
“…viridulum PPOs in the range of 55-75°C, and its inactivation curve is Derardja, Pretzler, Kampatsikas, Barkat, and Rompel (2017), who reported that apricot PPO loses more than 82% of its activity after 2 min of heat treatment at 70°C. The heat resistance of PPO varies with the reaction of enzymes with different substrates.…”
Section: Temperature Optimum and Stabilitymentioning
confidence: 99%
“…RA gradually decreased to 81.46% at 45 °C and showed a more rapid decrease to 61.64% and 45.14% at 55 and at 65 °C respectively. PPO is present in numerous (mature, immature, latent and active forms) isoforms, and its increased activity at 25 °C (TP) may be due to the presence of latent PPO [ 15 , 26 ]. In comparison, the results of HPCD treated quince juice showed that the RA decreased to 78.26%, 69.55%, 59.45% and 34.18% with increased temperatures of 25, 35, 45 and 55 °C respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore,i tw as suspected that the proenzyme undergoes self-cleavage,s evering the C-terminal domain from the pro-enzyme.W erecently observed asimilar process in apricot PPO,where the enzyme was spontaneously activated upon prolonged storage. [20] Thea ssumed selfcleavage of MdPPO1 was confirmed by SDS-PAGEo fp roenzyme solutions incubated at 4 8 8Cfor 20 days,indicating the activation of the pro-enzyme into its separated active and C-terminal domains ( Figure S1;s ee the Supporting Information for experimental details). To exclude the possibility that the observed self-cleavage was caused by contaminations originating from the expression host E. coli,f resh MdPPO1 enzyme was incubated with lysate of E. coli,w hich did not infer any change to the cleavage of MdPPO1 ( Figure S2).…”
mentioning
confidence: 83%